Patient-Reported Burden of Severe Alopecia Areata: First Results from the Multinational Alopecia Areata Unmet Need Survey - Bewley A; Figueras-Nart I; Zhang J; Guerreiro M; Tietz N; Chtourou S; Durand F; Blume-Peytavi U (Dove Medical Press, 2024)
Anthony Bewley,1 Ignasi Figueras-Nart,2 Jainzhong Zhang,3 Mariana Guerreiro,4 Nicole Tietz,4 Sami Chtourou,4 Frederick Durand,4 Ulrike Blume-Peytavi5 1Department of Dermatology, The Royal London Hospital & Queen Mary University, London, UK; 2Department of Dermatology, University Hospital de Bellvitge, Barcelona, Spain; 3Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of China; 4Eli Lilly and Company Ltd, Indianapolis, IN, USA; 5Charité - Universitätsmedizin Berlin, corporate member of Freie Universität Berlin and Humboldt-Universität zu Berlin, Department of Dermatology, Venereology and Allergology, Berlin, GermanyCorrespondence: Anthony Bewley, Department of Dermatology, The Royal London Hospital & Queen Mary University, London, UK, Tel +44 020 7767 3200, Email anthony.bewley@nhs.netPurpose: Alopecia areata (AA) is an autoimmune disease characterized by hair loss that has significant psychosocial implications. This study aims to describe the patient-reported burden of severe AA, coping mechanism and information needs using data from the multinational AA Patient Satisfaction and Unmet Need Survey.Patients and Methods: Participants with current or previous ≥ 50% scalp hair loss (n = 747) were recruited from 11 countries and completed a web-based survey that assessed demographics, clinical characteristics, disease burden and psychosocial impact. Data were stratified according to sex, current age, disease duration and current severity of scalp hair loss.Results: The mean (SD) age of participants was 43.8 (7.1) years, 55.3% were women, and 63.5% reported AA symptoms within 6 months of diagnosis. Most participants had black or brown hair (88.4%), reported a disease duration of 2 years or more (75.6%) and had current scalp hair loss of ≥ 50% (87.4%). Severe hair loss also extended to eyebrow (46.9%), eyelash (48.7), beard (61.5%) and body hair (73.2%). Participants commonly reported comorbidities such as anxiety (26.1%), depression (18.1%) and sleep problems (28.1%). The Dermatology Life Quality Index revealed a severe impact on quality of life; 86.2% of participants scored > 10. Mental health/mood was significantly affected; 55.8% of participants reported a substantial impact. Long-term effects included decreased self-esteem (32.9%), poor mental health (28.1%) and challenges in day-to-day activities (27.2%). Information needs were centered around treatment expectations, mental health, and available treatment options. More severe symptoms and a greater daily impact were reported by women and those with a longer disease duration.Conclusion: The study emphasizes the substantial burden, including impaired quality of life and psychological well-being, of severe AA on the lives of surveyed participants. The findings highlight the importance of comprehensive disease management strategies that address both physical and psychosocial aspects of AA.Plain language summary: Alopecia areata (AA) is a disease that results in hair loss and can greatly affect quality of life and well-being. The authors wanted to understand how this condition affects people's lives and what they need to cope with it. A survey was completed by adults from 11 different countries who had current or past severe AA. The participants were asked about their demographics, their experiences with the condition and how it impacted their daily lives. The results showed that AA has a severe impact on their quality of life, including their mental health and daily activities. Participants also experienced decreased self-esteem and faced challenges in their relationships and daily routines, and many reported feeling anxious, depressed, and having trouble sleeping. Participants found different ways to cope with their condition and expressed a need for realistic expectations about treatment results, information about mental health, and treatment options. The study also found that women and those with a longer duration of AA tended to have more severe symptoms and the impact on their lives was greater. Overall, this study shows that current or previous episodes of severe AA had a significant impact on people's lives, including their mental health and daily activities. It emphasizes the need for information about the condition and treatment options with realistic expectations. The findings help to better understand the experiences of people with AA and may aid the provision of appropriate support and information.Keywords: burden of disease, quality of life, disease management